دور الأنظمة العربية في اغتيال فلسطين ونكبة 1948 : The Role of the Arab Regimes in the Assassination of Palestine and the Nakba of 1948 - Amezzian, Mohammed (Journal of Al-Tamaddun, 2021)
This research discusses the historical backgrounds that led to the Zionist occupation of Palestine. It demonstrates the significant contrast between the official and popular positions in dealing with the Zionist project that began its invasion to Palestine at the beginning of the 20st century. The research demonstrates the role of the Palestinian leaders who were supported by the popular Islamic and Arab movements in intensifying resistance and military conformation against the British mandate and Jewish armed groups. In addition, the research identifies the most prominent military achievements of the armed resistance. This paper also documents the negative role of the official Arab regimes in deterring the popular revolutions and containing the developing of military rebellions. More importantly, this research has proven that the official position of the Arab governments served against the Palestinian cause by preventing the genuine armed popular movements from fighting the Zionist project, which had consequently led to the defeat (Nakba) of 1948. To study the official position of Arab leaders, the research puts emphasis on four elements: Adoption of a protest diplomacy, Exclusion of the military solution to confront the Zionist project expansion, Acceptance of the United Nations Resolution regarding the partition of Palestine which shapes the first core for establishing the Jewish State, and finally Acceptance of the ceasefire after 1948 war which represents a recognition of the right of existence of the Jewish State.